Adaptação de dois programas psicoeducativos para pessoas que cuidam de familiares com transtorno neurocognitivo maior (demência): ComTato e iSupport - Campos, Camila Rafael Ferreira (2021)
The psychoeducational programs that are offered to caregivers who assist a family member with a major neurocognitive disorder (NCD, or dementia) typically have only modest effects on the mental health of the participants. The programs with the strongest effects are based on the cognitive-behavior therapy model of behavior change, and address context-specific demands. Two programs with these same characteristics are iSupport, a program prepared for the World Health Organization (WHO), and ComTato, a Brazilian program. Given their potential to contribute to caregivers’ mental health, it is important to obtain further evidence about the effects of these programs. With respect to iSupport, an on-line, self-help program, the objective was to evaluate an adapted version of the program, for use in Brazil (Studies 1 and 2). With respect to the ComTato program, offered via synchronous and individualized sessions, the objective was to evaluate the effects of this program, when offered on-line (Studies 3 and 4). In Study 1, the iSupport material, written in English, was translated into Brazilian Portuguese and the text was revised by experts in Gerontology. Next, nine (ex)caregivers assisting a family member with a major NCD and six healthcare professionals working with the elderly examined the material individually and then discussed their suggestions for the program in focus groups. These suggestions were analyzed by the research team for this project, and then approved by the WHO, resulting in the first Brazilian version of this program. In Study 2, the acceptability and usability of the iSupport-BR program were evaluated by five caregivers of people with a major NCD, after they used the program via a digital platform. Their evaluations were positive, and further changes to the program were made in response to suggestions they made that were approved by the research team. In Study 3, to examine the effects of the ComTato program, an experimental, multiple-baseline research design was used. Participants were 22 family caregivers who assisted an elderly person with Alzheimer’s disease (AD). Seven caregivers started in the control group (CG), then entered the intervention group (IG); thus there were 15 caregivers in the IG, and 14 in the CG. Evaluations were made of the caregivers’ knowledge about AD and other topics related to the socioemotional demands of caregiving, burden, coping strategies, quality of the caregiver-older person relationship, and perceptions of the effects and acceptability of the intervention program. Based on comparisons of the pre and posttest scores for the IG caregivers, differences were found for most of the measures, with effect sizes that were moderate to large, indicating important benefits for the participants of the ComTato program. These benefits were confirmed based on a comparison of the changes observed for the caregivers in the IG and the CG. In Study 4, effects of the ComTato program using the new, on-line format were compared with results from previous studies, using an in-person format. The caregivers who received in-person visits had larger gains in knowledge for some concepts, compared to the caregivers who participated on-line. However, no differences were found for the socioemotional variables, suggesting that both formats are effective. The positive effects of these two programs, iSupport BR and ComTato, increase the evidence that supports the possibility of offering these programs to caregivers assisting a family member with a major NCD. In addition, these results add examples and increase our knowledge about the adaptation of intervention programs in prevention and promotion of mental health, in Brazil.